Scorpionism in Ecuador: First report of severe and fatal envenoming cases from northern Manabí by Tityus asthenes Pocock. (October 2015) - Borges, Adolfo; Morales, Melva; Loor, Wilmer; Delgado, Miguel
Abstract: The presence in rural areas of western Ecuador of scorpions in the genus Tityus capable of producing pediatric mortality is hereby evidenced. The medical significance of scorpions in Ecuador has been underestimated partly because of the clinically unimportant stings delivered by Centruroides margaritatus and Teuthraustes atramentarius, which have venom with low toxicity to vertebrates. Five intra-domiciliary cases of scorpion envenoming in victims aged between 1.9 and 16 years old, including one fatality, are reported from rural settings in forest areas of Chone (n = 2) and Flavio Alfaro (n = 3) counties, northern Manabí province, western Ecuador. Three cases were graded as Class II (moderate) and two in Class III (severe) envenoming. Manifestations showed characteristic autonomic nervous system hyper-stimulation and the fatality (a 1.9-year-old boy from Flavio Alfaro) was due to cardio-respiratory failure. Marked leukocytosis in four of the cases (21, 800–31, 800 cells/mm 3 ), with notable neutrophilia (58–82%), suggests induction of a venom-mediated systemic inflammatory response-like syndrome. Specimens responsible for cases in Flavio Alfaro County, including the fatality, were classified as Tityus asthenes Pocock, accountable for severe scorpionism in Colombia. These findings demand implementation of control and therapeutic measures in affected areas in Ecuador, including evaluation of available scorpion antivenoms. Highlights: Pediatric mortality due to scorpion envenoming is reported from Ecuador for the first time. This is the first report including taxonomical verification of a fatal case due to Tityus asthenes. The mountainous area of northern Manabí, western Ecuador, is described as a new endemic area of scorpionism. The lack of scorpion antivenom in Ecuador demands the assay of available anti- Tityus antidotes.